Genomic Association Study for Cognitive Impairment in Parkinson's Disease - Park, Kye Won; Jo, Sungyang; Kim, Mi Sun; Jeon, Sang Ryong; Ryu, Ho-Sung; Kim, Jinhee; Park, Young-Min; Koh, Seong-Beom; Lee, Jae-Hong; Chung, Sun Ju (Frontiers in Neurology, 2021)
Background: Cognitive impairment is very common in Parkinson’s disease (PD) and constitutes the most debilitating complication of this disease. However, to date, few studies have investigated genome-wide association in the development of cognitive impairment of PD. We aimed to identify the genetic loci associated with cognitive impairment in patients with sporadic PD by ethnicity-specific genotyping. Materials and Methods: We recruited 1,070 patients with PD and performed a genome-wide association study using the Korean Chip, a microarray chip containing 827,400 single nucleotide polymorphisms (SNPs) optimized for the Korean population. Multiple logistic regression models adjusting for age, sex, years of education, and disease duration were used to compare between patients with and without cognitive impairment, which was defined using the Mini-Mental Status Examination (MMSE) score (MMSE score ≥26 versus <26) or the Montreal Cognitive Assessment (MoCA) score (MoCA score ≥24 versus <24). Results: RYR2 SNP rs10495397 was most significantly associated with cognitive impairment based on the MMSE scores (OR = 3.21; 95% CI = 1.96-5.25, P = 3.36 × 10-6) and CASC17 showed the strongest association with cognitive impairment based on the MoCA scores. However, none of the SNPs were statistically significant after Bonferroni correction. Conclusion: RYR2 may play a role in cognitive impairment in PD by the pathogenic mechanism of neuroinflammation. However, more studies are needed to replicate and validate the results of our functional study.